PENENTUAN WAKTU PARO BIOLOGI TC99M MDP PADA PEMERIKSAAN BONE SCANNING - Titi Purwati; Wahyu Setiabudi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Nuclear medicine is a branch of medical science to know the anatomy and physiology of the body. One type of nuclear medicine examination is the examination of bone scanning. According to UNSCEAR (United Nations Scientific Committee on the Effects of Atomic), examination of bone scanning is a type of diagnostic examination which has the largest contribution. Examination of bone scanning using a radiopharmaceutical activity is very high around 320-740 MBq. Because the activity of a given patient is very high, it is necessary to note a half-life in bone biology for radiation protection purposes. Has conducted research on 35 patients in the examination bone scanning to determine the biological half time and the correlation between activity and biological half time. Radioisotopes are used in this examination is Tc99m with farmaka MDP kit (Methylene Diphosponat) with a half-life of 6.03 hours. On examination, the MDP Tc99m radiopharmaceutical is injected intravenously into the patient's arm as much as 15-20 mCi. Furthermore, patients will wait for ± 3 hours and after the enumeration for 10 minutes. Imaging results obtained from the average of the beginning of 627493360 Bq activity and activity after 3 hours of 15290043.495 Bq. Then from the calculation of activity against time t obtained decay constant is effective with an average of 0.271 h1, the mean decay constants of physics-1 and the average 0,115 hours of biological decay constant of 0.156 h-1. The decay obtained from biological half time with an average of 4.434 hours. In this study also found a correlation between the activity after 3 hours with a half-life of -0.94 biology, because the correlation value close to -1 (negative one) then the relationship of these variables have a strong negative correlation.